Thematic Network related to partner selection in strategic alliances( study Case: Iranian medical tourism businesses)) - Ali Asghar Shalbafian (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2020)
Strategic alliances have come to prove instrumental across various industries owing to rapidly evolving and competitive world. Partner selection plays core and key role in any strategic alliance formation and its outcome. Though voluminous studies targeted partner selection in general, the subject has rarely investigated in tourism industry particularly in the context of a tourism type i.e. medical tourism and a specified market i.e. Iran. To this end, 17 medical tourism experts have been recognized by snowball sampling. Data have been gathered through semi-structured interviews and analyzed with Maxqda 10 software based on theme analysis. Findings show that 3 main themes including prior relation and cognition, probing about partner and partner characteristics can affect on medical tourism alliance formation in Iran.